In vitro Shoot Multiplication of Withania coagulans (Stocks) Dunal (Plant Tissue Culture and Biotechnology, 2016)
Withania coagulans (Stocks) Dunal is an important medicinal plant of Solanaceae. Nodal segments obtained from field grown plants were used as explants. 1 ? 2 cm long nodal segment with a single one bud was cultured on MS containing 2.5 mg/l thidiazuron (TDZ), 0.1 mg/l NAA and 50 mg/l adenine sulphate (AdS) resulted in formation of 5.16 shoots per node. However, vitrification was observed in all explants within one month. On the other hand nodal explants cultured on MS supplemented with 2.50 mg/l meta?topoline (mT) with 0.1 mg/l NAA and 50 mg/l AdS resulted in the formation of 4.50 healthy and uniformly grown shoots per node.Plant Tissue Cult. & Biotech. 26(2): 187-195, 2016 (December)